ANALYSIS OF THE FLYPAPER EFFECT IN TESTING THE EFFECT OF REGIONAL OWN-SOURCE REVENUES AND FISCAL BALANCE TRANSFER ON REGIONAL EXPENDITURES (STUDY ON REGENCIES AND MUNICIPALITIES IN CENTRAL JAVA FROM 2017-2020) - Anis Rohmi Fitriana; Maya Widyana Dewi; Wikan Budi Utami (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the flypaper effect in testing the effect of Regional Own-source Revenue and financial balance transfer on Regional Expenditures in Regencies and Municipalities in Central Java from 2017-2020. The data analysis method in this study uses descriptive statistical test, classical assumption test using normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Hypothesis testing used multiple linear regression test, F test (model feasibility test), t test (partial), coefficient of determination test (R2), and flypaper effect analysis. Based on the results of the F test (model feasibility test), it shows that the regression model is feasible to use in this study. Then partially Regional Own-Source Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) have a significant positive effect on Regional Expenditure. Meanwhile, Revenue Sharing Fund (DBH) has no significant effect on Regional Expenditure. The results of this study indicate that the coefficient value of the General Allocation Fund (DAU) variable is greater than the coefficient value of Regional Own-Source Revenue (PAD), this illustrates that there has been a flypaper effect on Regional Expenditure in Regencies and Municipalities in Central Java from 2017-2020. Keywords: Flypaper Effect, Regional Own-Source Revenues, Fiscal Balance Transfer, Regional Expenditures